Two cases of mother-to-child transmission of HIV and Trypanosoma cruzi in Argentina - Agosti, Maria Rosa (2012)
In this article we describe two lethal cases of MTCT of HIV and T.cruzi in the province of Buenos Aires, Argentina. Child 1 was admitted to the hospital being 1 month old with respiratory difficulty and diarrhoea. Being six months old he was released but being 22 months old he presented sepsis and died. The mother was not treated during pregnancy, while the child was treated with combined HAART and benznidazol. Child 2 was admitted to a provincial Hospital being 20 days old, and referred to the Children´s Hospital. After 39 days at the ICU the child died with sepsis. His mother received ZDV late in her pregnancy. The child received was treated with HAART, interrupted at 3 months due to severe organic failure. The lack of diagnosis of T. cruzi in both mothers worsened the prognosis of these two children, since treatment with antiparasitic drugs is used since birth.